(untitled) (Asian Journal of Medical Sciences, 2024)
Background: Pregnancy is a stressful test for the mother’s thyroid function. The frequency of hypothyroidism in pregnant women is high. However, there are no adequate studies to evaluate the adverse effects of subclinical hypothyroidism (SCH) during pregnancy. Aims and Objectives: This study was carried out to evaluate the prevalence of SCH in pregnancy and its adverse feto-maternal outcomes among mothers attending a tertiary care teaching hospital in Darjeeling district, West Bengal, India. Materials and Methods: The present study was an institution-based observational descriptive study with a prospective longitudinal design conducted for 1 year among pregnant women attending the antenatal clinic of the study institution in the first trimester of their pregnancy. The sample size for the present study was calculated to be 200. A consecutive sampling technique was utilized. The enrolled women were evaluated for thyroid status by assessing serum thyroid stimulating hormone and free T4 level. All the enrolled mothers were kept under close follow-up and they were evaluated for the development of any antenatal, intranatal, and postnatal complications. Results: The mean age was found to be 23.1±4.2 years, most of the women were nulliparous (60%). Of the women, 74% were euthyroid, while the prevalence of SCH was found to be 16%. On follow-up till the termination of their pregnancies, mothers suffering from SCH had statistically significantly higher incidence of maternal complications such as hypertensive disorders in pregnancy (P=0.001), abortion (P<0.001), postpartum hemorrhage (P=0.020) and also fetal adverse outcomes, such as intrauterine growth restriction (P=0.018), fetal premature birth (P=0.035), and low birth weight (P=0.004) when compared with euthyroid mothers. Conclusion: The burden of SCH high in the study population, and it was significantly associated with a number of different maternal as well as fetal complications and adverse outcomes.